2019
DOI: 10.1021/jacs.9b11716
|View full text |Cite
|
Sign up to set email alerts
|

α-C–H Functionalization of π-Bonds Using Iron Complexes: Catalytic Hydroxyalkylation of Alkynes and Alkenes

Abstract: The discovery of catalytic systems based on earth-abundant transition metals for the functionalization of C–H bonds enables streamlined and sustainable solutions to problems in synthetic organic chemistry. In this Communication, we disclose an iron-based catalytic system for the functionalization of propargylic and allylic C–H bonds. Inexpensive and readily available cyclopenta­dienyliron­(II) dicarbonyl complexes were employed as catalysts for a novel deprotonative activation mode for C–H functionalization, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
33
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 66 publications
4
33
0
Order By: Relevance
“…A precoordination of the alkyne to the titanium center to give an alkyne-titanium π-complex ( X ) is suggested to lower the p K a of the propargylic hydrogen atom(s) in the first place. 19 Even though this type of reactivity is very rare for titanium imido complexes, it was observed for reversible C(sp 3 )–H activation processes in the case of alkanes. 2 b ,20 Just recently, Tonks et al also observed propargylic C–H activation of 3-hexyne by a titanium bisamido complex.…”
Section: Resultsmentioning
confidence: 99%
“…A precoordination of the alkyne to the titanium center to give an alkyne-titanium π-complex ( X ) is suggested to lower the p K a of the propargylic hydrogen atom(s) in the first place. 19 Even though this type of reactivity is very rare for titanium imido complexes, it was observed for reversible C(sp 3 )–H activation processes in the case of alkanes. 2 b ,20 Just recently, Tonks et al also observed propargylic C–H activation of 3-hexyne by a titanium bisamido complex.…”
Section: Resultsmentioning
confidence: 99%
“…With a suitable catalyst and an operational catalytic system in hand, we sought to expand the electrophile scope to generate more synthetically applicable products. 46 We were drawn to aldehydes as starting materials due to the ready availability of the functional group and the synthetic versatility of the homopropargylic alcohol products that would result.…”
Section: Hydroxyalkylation Development and Scopementioning
confidence: 99%
“…The latter process is completely atom economic, avoids the use of stoichiometric metal and/or costly substrates and the generation of stoichiometric metal salt waste, and could be achieved via sequential deprotonation-propargylation-protonation in a catalytic manifold. This type of chemistry constitutes a catalytic asymmetric propargylic C-H functionalization 3 11 but to be the best of our knowledge has no literature precedent. In the recently-reported racemic case, 11 aldehyde substrates possessing α-C(sp 3 )-H bonds are not permitted.…”
Section: Introductionmentioning
confidence: 99%
“…This type of chemistry constitutes a catalytic asymmetric propargylic C-H functionalization 3 11 but to be the best of our knowledge has no literature precedent. In the recently-reported racemic case, 11 aldehyde substrates possessing α-C(sp 3 )-H bonds are not permitted. Such substrates are challenging and appear not conceptually feasible under typical basic conditions as the propargylic protons are much less acidic ( p Ka >30) than aldehyde α-hydrogens ( p Ka ~17) in an ionic reaction manifold ( Figure 1B ).…”
Section: Introductionmentioning
confidence: 99%